Speed segmentation on exchanges: Competition for slow flow - Lisa Anderson; Emad Andrews; Baiju Devani; Michael Mueller; Adrian Walton (Bank of Canada, 2018)
In 2015, TSX Alpha, a Canadian stock exchange, implemented a speed bump for marketable orders and an inverted fee structure as part of a redesign. We find no evidence that this redesign impacted market-wide measures of trading costs or contributed appreciably to segmenting retail order flow away from other Canadian venues with a maker-taker fee structure. This suggests that Alpha attracts already-segmented flow from venues with fee structures other than maker-taker. Some heavy users of Alpha trade off improvements in fill rates and execution size against mildly larger effective spreads and price impacts. These heavy users also utilize larger market orders and fewer spray orders.
Keywords: G14; G24; 330; Financial markets; Market structure and pricing